Dietary patterns and diabetes mellitus among people living with and without HIV: a cross-sectional study in Tanzania - Malindisa, Evangelista; Dika, Haruna; Rehman, Andrea M.; Olsen, Mette Frahm; Francis, Filbert; Friis, Henrik; Faurholt-Jepsen, Daniel; Filteau, Suzanne; PrayGod, George (Frontiers in Nutrition, 2023)
Background: Due to the complexity of human diets it is difficult to relate single foods to health outcomes. We aimed to identify the dietary patterns and associated factors and to assess the association of dietary patterns with prediabetes/diabetes among HIV-infected and HIV-uninfected adults. Methods: Diet data were collected by a food frequency questionnaire (FFQ) and dietary patterns were derived by principal component analysis (PCA) and reduced rank regression (RRR). The association between dietary patterns and associated factors as well as with prediabetes/diabetes was assessed using multinomial logistic regression. Results: Of 572 recruited, 63% were HIV-infected. The mean (±SD) age was 42.6 (±11.7) years and 60% were females. The PCA identified two major dietary patterns i.e. vegetable-rich pattern (VRP) and vegetable-poor pattern (VPP) whereas RRR identified one dietary pattern: carbohydrate-dense pattern (CDP). Compared to females, males had higher concordance with VPP and CDP, but less with VRP. Higher socioeconomic status had higher concordance with VRP and VPP but low concordance with CDP. Compared to HIV-negative participants, HIV-infected people had higher concordance with VRP but less with CDP. Compared to younger people, older people had lower concordance with VPP. High concordance with CDP or VRP was positively associated with prediabetes. Higher concordance with VRP was associated with a borderline decrease in diabetes. No association was observed between VPP with either prediabetes or diabetes. Conclusion: Our findings suggest that dietary patterns may impact the risk of prediabetes and diabetes differently. Awareness of the health benefits of VRP should be encouraged in the community, especially for men who seem to consume fewer vegetables. Longitudinal studies are needed to explore the contribution of dietary patterns to prediabetes/diabetes development in sub-Saharan Africa.